2012
DOI: 10.1371/journal.pone.0042388
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 34 Novel Proinflammatory Proteins in a Genome-Wide Macrophage Functional Screen

Abstract: Signal transduction pathways activated by Toll-like Receptors and the IL-1 family of cytokines are fundamental to mounting an innate immune response and thus to clearing pathogens and promoting wound healing. Whilst mechanistic understanding of the regulation of innate signalling pathways has advanced considerably in recent years, there are still a number of critical controllers to be discovered. In order to characterise novel regulators of macrophage inflammation, we have carried out an extensive, cDNA-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…We have previously identified multiple regulators of inflammatory signaling in macrophages by genome-wide expression screening for genes which drove expression of the inflammatory chemokine Cxcl2 when transfected into RAW 264.7 cells (21); TMEM203 was one such protein. Multiple alignment of TMEM203 orthologs from a wide range of species demonstrated that TMEM203 is an evolutionally highly conserved gene ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified multiple regulators of inflammatory signaling in macrophages by genome-wide expression screening for genes which drove expression of the inflammatory chemokine Cxcl2 when transfected into RAW 264.7 cells (21); TMEM203 was one such protein. Multiple alignment of TMEM203 orthologs from a wide range of species demonstrated that TMEM203 is an evolutionally highly conserved gene ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous functional screens discovering novel regulators of inflammation (21), we reported the identification of TMEM203 as a previously unknown proinflammatory gene in mouse macrophages (21). Here, we demonstrate that TMEM203, a protein that was recently shown to be endosomal and interacts with the pleiotropic inositol phosphate signaling pathway protein IP3R (22), is associated with SLE disease activity, forms a functional and ligand-dependent complex with STING, and promotes its translocation to endo-lysosomes.…”
mentioning
confidence: 99%
“…11,12 Defects in these clearance mechanisms appear to be associated with persistent tissue inflammation and autoimmunity to cellular contents. 13,14 Tissue damage resulting from uncontrolled acute inflammatory responses causes discomfort and severely compromises normal tissue function. 15 In both acute and chronic models of inflammation, endogenous resolvins have been shown to accelerate resolution of inflammation.…”
Section: Role In Resolution Of Inflammationmentioning
confidence: 99%
“…High-throughput screening was carried out in high throughput robotics facility in the university of Sheffield [11]. Human liver HepG2 cells were seeded in 96 well tissue plates at concentration 2×10 5 cells/ml.…”
Section: High-throughput Screening Of the Cell-based Ldl Uptake Assaymentioning
confidence: 99%